PENERAPAN MODEL PEMBELAJARAN TARI BAMBU UNTUK MENINGKATKAN HASIL BELAJAR PKn PADA SISWA KELAS IV SDN 1 WATES KECAMATAN KEDUNGJATI KABUPATEN GROBOGAN - Sitepu, Melyani Sari (Faculty of Teacher Training and Education of Undaris, 2017)
This research is based on the low learning outcomes of fourth grade students of SDN 1 Wates. The formulation of the problem is whether the application of bamboo dance model can improve the learning outcomes of Civics in fourth grade students SD Negeri 1 Wates Kedungjati District Grobogan District by using bamboo dance model. Type of research used is classroom action research using Arikunto model. The study was conducted on July 20 to August 3, 2017 in SDN 1 Wates. Technique of collecting data in this research is by test and non test. The test to measure student's civics learning outcomes, while non test to measure teacher's skill and student activity in Civic learning by using model of Bamboo Dance application at SDN 1 Wates. Data analysis uses quantitative data analysis to cultivate learning outcomes and qualitative analysis to process teacher skills data and student activity in learning. The results showed that the use of Bamboo Dance model can improve the learning outcomes of fourth grade students of SDN 1 Wates Kecamatan Kedungjati Grobogan District. It can be shown by the improvement of the result of fourth grade student learning in each cycle obtained data on cycle I, average class 68,3 mastery with classical completeness of 11 students or 45,8%. In the implementation of the action cycle II obtained data learning results with average class 91.2 and 100% complete percentage. Based on the data, it can be concluded that the result of science learning of fourth graders has fulfilled the success indicator that is at least 70% of students reach KKM â‰¥70 with class average grade 91,2, from pre cycle to cycle II increased by 15 students or 62,5%.